PHYTOCHEMICAL SCREENING AND QUANTITATIVE ESTIMATION OF TOTAL PHENOLIC CONTENT AND TOTAL FLAVONOID CONTENT OF GRAINS OF PASPALUM SCROBICULATUM - Sharma s; SAXENA J (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Paspalum scrobiculatum, commonly known as â€˜Kodo' is a millet variety found in India having medicinal and pharmaceutical importance. Crude extracts of chloroform, ethyl acetate, ethanol and methanol were evaluated for the presence of total phenolic content and total flavonoid content of the millet grains. Phytochemical screening was done for a qualitative basis of the study. Phytochemical tests showed the presence of phenolics and flavonoids in more polar solvent, methanol and ethanol. Carbohydrates and fats and oils were present in all four extracts.Â The result of total phenolic content by Folin- ciocalteu method with gallic acid as standard at 765 nm ranged from 40.15 Â± 0.17 to 175.94 Â± 1.018 Âµg/100Âµg extract. Ethanol extract showed maximum phenolic content. The total flavonoid content at 510 nm using rutin as standard ranged from 4.88 Â± 0.50 to 116.48 Â± 1.57 Âµg/100Âµg extract. Highest flavonoid content was found in ethanol extract. Presence of good amount of phenolic and flavonoid content indicates presence of phytochemicals in kodo millet having good antioxidant potential. Keywords: Paspalum scrobiculatum, Phytochemical, TPC, TFC, Ethanol, etc.